Elevated Plasma Levels of Interleukin-12p40 and Interleukin-16 in Overweight Adolescents - Lichtenauer, Michael (Biomed Res Int, 2015)
Introduction. Obesity during adolescence is an increasing problem for both the individual and health care systems alike. In Western world countries, childhood adiposity has reached epidemic proportions. It is known that elevated levels of proinflammatory cytokines can be found in the plasma of obese patients. In this study, we sought to determine the relation between IL-12p40, IL-12p70, and Interleukin-16 (IL-16) in overweight adolescents. Materials and Methods. Seventy-nine male Caucasian adolescents aged 13–17 years were included in this study. Thirty-seven of them had a body mass index (BMI) above the 90th age-specific percentile. Il-12p40, IL-12p70, and IL-16 were measured from plasma using Luminex multiplex technology. Results. Both IL-12p40 and IL-16 concentrations were significantly increased in overweight subjects compared to normal weight controls (IL-12p40: 1086.6 pg/mL ± 31.7 pg/mL SEM versus 1228.6 pg/mL ± 43.5 pg/mL SEM; IL-16 494.0 pg/mL ± 29.4 pg/mL SEM versus 686.6 pg/mL ± 52.5 pg/mL SEM, P < 0.05 and P < 0.01, resp.). No differences were found for IL-12p70. Conclusions. Based on these results, we believe that the increased levels of IL-12p40 and IL-16 are associated with an ongoing inflammatory response in obese individuals and could lead to the development of disease conditions related to obesity.